A Critical Appraisal of Ethical issues in E-Learning - Anjankar A J; Mohite P M; ,Waghmode A; Patond S; Ninave S (Institute of Medico-legal Publications Pvt Ltd, 2021)
Covid-19 pandemic left a long lasting impact on entire education sector, as an estimated 90% of educational institutions closed down in at least 188 countries in the world and offline traditional teaching came to a standstill. In such critical situation pedagogical innovations in form of online education, virtual simulators etc came to rescue to keep the students academically occupied and motivated entering into the virtual era.With advent of online education, several issues like social, infrastructural & pedagogical and psychological issues came to fore. Social divide, geographical issues, technical support and know how etc added to the gravity of situation. Educationists also pointed out that ethical issues in e-learning like academic dishonesty, plagiarism and copyright violations need to be addressed.The present work is an attempt to find out various ethical issues in online education and to make suggestions, where ever required.